Synthesis and characterization of bio-adhesive using natural rubber latex and bio-based fillers for medium density fibreboard manufacturing - Jayshree, Thuraisingam (2019)
The over-exploitation of synthetic adhesives in wood composite manufacturing industries has become a major threat to environment and consumers’ health due to its carcinogenic formaldehyde emissions. In order to overcome this issue, this study has been focused towards the development of bio-based adhesive from natural rubber latex (NRL) incorporated with rice starch (RS) and lignin as the fillers, by blending technique.These fillers are vital in order to enhance the mechanical properties of NRL and thus, their respective compatibility with the base material upon blending is compared.. Prior to the blending, RS were subjected to chemical modification using hydrochloric acid (HCl) and sodium hydroxide (NaOH). Acid hydrolysis of 1M HCl for 60 minutes at 55°C and alkaline hydrolysis using 2M NaOH for 60 minutes at 45°C yielded modified RS with the best working shear strength of 0.38MPa and 0.43MPa respectively. Both acid and alkali modified RS were blended with NRL in weight content of 0%,25%,50%,75% and 100% accordingly.The bio-adhesives were characterized physically into gel time, viscosity and solid content. Consequently, all formulations were applied for medium density fibreboard(MDF) manufacturing via hot pressing at 180°C for 4 minutes and board specimens were characterized mechanically in terms of modulus of rupture(MOR), modulus of elasticity (MOE), internal bonding(IB) and thickness swelling(TS). Thermal stability is analyzed through thermogravimetric analysis (TGA) while the chemical interaction that resulted through incorporation of fillers with NRL is studied through Fourier transform infrared spectroscopy(FTIR) and the morphological analysis is observed through scanning electron microscopy(SEM). The results indicated that bio-adhesive formulation that contains the highest by weight content of acid and alkali modified RS exhibited outstanding MOR of 26.4MPa and 36.7MPa while IB of 0.39MPa and 0.66MPa respectively. As an overall, alkali modified RS exhibited greater mechanical adhesive performances compared to HCl modified RS. Moreover, thermal analysis proved that RS content by weight of 75% in bio-adhesive formulation exhibited significant weight loss at 361.73 °C, indicating that incorporation of RS actually enhances the thermal oxidative stability of bio-adhesive. The second part of this study revolves around the development and application of bio-adhesive from NRL, incorporated withE. Blending with NRL was performed by varying filler weight content (0%,25%,50%,75%,100%).Similar physical, mechanical, morphological and thermal analysis were investigated. Samples bonded with NRL-EHL bio-adhesives showed deteriorating effect on the MOR and IB values of MDF, where MOR declined from 15MPa to 4MPa when EHL loading was increased from 25wt% to 100wt% due to incompatibility between EHL and NRL matrices. Alkaline activation of EHL using 3M NaOH was applied to improve the performance of EHL based bio-adhesive. Consequently, bio-adhesive formulation with equivalent weight content of NRL and NaOH activated EHL exceeded ASTM standard requirement by yielding MDF with MOR of 36 MPa. The IB recorded was 0.75MPa which proved that alkaline modification of EHL enhanced the dispersion of filler into NRL matrix and caused better cross-linking between bio-polymers. Thoroughly, alkaline activated EHL incorporation into NRL formulation gave better physical, mechanical and thermal performance of the bio-adhesives compared to modified RS and EHL. As a conclusion, this study serves as a platform to prove that bio-polymers such as RS and EHL can be viable filler for NRL, with activated EHL to be the best option of fillers.